Use of multiparametric magnetic resonance in the active surveillance of prostate cancer: An integrative review (Research, Society and Development, 2024)
Introduction: Prostate cancer is the second most common malignancy in males, with an increasing incidence due to improvements in diagnostic methods, such as multiparametric magnetic resonance imaging (MRI). Given this, new therapeutic modalities, such as active surveillance (AV), which is indicated for low-risk prostate cancer, are gaining ground. Objective: To investigate the use of mpMRI for monitoring patients undergoing active surveillance as a treatment for prostate cancer. Methods: This is an integrative review carried out using the SciELO, PubMed ®, VHL and LILACS databases. In total, 389 studies were found, after applying the inclusion and exclusion criteria, 17 articles remained chosen. Results: 5,206 patients with prostate cancer were analyzed in 15 studies, as there was no sample in 2 selected articles. Some studies assessed that mpMRI was not sufficient for monitoring VA patients with prostate cancer, with an indication for supplementation with biopsy even when there was no indication of disease progression on mpMRI. Despite this, most of the selected studies concluded that mpMRI had a negative predictive value for prostate cancer progression and could be used for follow-up in VA patients, with improvement if related to other variables such as prostate-specific antigen levels. Conclusion: mpMRI is gaining importance in the evaluation of patients with prostate cancer, including the indication and follow-up of patients in VA. Despite some limitations, it can be used in conjunction with other components to assess disease progression.